1984
DOI: 10.1136/jnnp.47.3.250
|View full text |Cite
|
Sign up to set email alerts
|

Deficient learning and memory in early and middle phases of multiple sclerosis.

Abstract: SUMMARY Forty-three patients with multiple sclerosis showed disturbances in short-term memory, learning, and delayed recall which were associated with years of active disease (average was 4.5 years), age, presence of flareup, but not steroid/ACTH treatment. Unrecognised memory loss might be prevalent early in the natural history of multiple sclerosis and deserves neuropsychological assessment.Cognitive decline commonly occurs in the later stages of multiple sclerosis.' In the past three decades some of the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0
7

Year Published

1986
1986
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(82 citation statements)
references
References 19 publications
6
69
0
7
Order By: Relevance
“…The results here presented are in agreement with several reports of normal verbal and visuospatial span 8,10,[12][13][14][22][23][24] .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results here presented are in agreement with several reports of normal verbal and visuospatial span 8,10,[12][13][14][22][23][24] .…”
Section: Discussionsupporting
confidence: 93%
“…The WMS Logical Memory and similar story recall tests are consistently found to be impaired in patiens with MS 12,13,23,28 , as well as the difficult pairs and the delayed testing of paired associates 8,13,24,35 . Visual reproduction was also found to be impaired by Rao et al 13 in chronic progressive patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent studies have confirmed the high incidence of cognitive disturbances in patients with MS (Kahana et al, 1971;Kurtzke et al, 1972;Staples & Lincoln, 1979;Grant et al, 1984;Rao et al, 1984;Filley et al, 1989;Franklin et al, 1990;White, 1990) and it has been suggested that MS be considered a form of "subcortical" dementia, characterized by deficits in visuospatial and memory functions with intact verbal skills (Caine et al, 1986;Rao, 1986). However, other authors have reported also verbal and language loss in MS patients including deficits on the WAIS vocabulary test, naming, reading, and verbal fluency (Diers & Brown, 1950;Jambor, 1969;Ivnik, 1978;Grant et al, 1984;Heaton et al, 1985).…”
Section: To the Editormentioning
confidence: 89%
“… Συνήθως εκδηλώνονται με διαταραχή μνήμης (Rao SM, 1984, Grant I, 1984, Beatty WW, 1988) ή μείωσης της ταχύτητας επεξεργασίας πληροφοριών από τον εγκέφαλο (Beatty WW, 1988, Litvan I, 1988, Rao SM, 1989, Janculjak D, 1999, αφασικές διαταραχές , Okuda B, 1996, λόγω μαζικής απομυελινωτικής βλάβης του επικρατούντος ημισφαιρίου (Kahana E, 1971), ή ψυχικές διαταραχές, κυρίως του συναισθήματος, όλες φλοιώδους προέλευσης. Σε ένα μικρό ποσοστό ασθενών με ΣΚΠ μπορεί να εκδηλωθεί πρώιμα «υποφλοιώδης» άνοια (Young AC, 1976, Gordon FS, 1996.…”
Section: ) γνωσιακές διαταραχέςunclassified